Wien und die jüdische Erfahrung 1900-1938 Akkulturation - Antisemitismus - Zionismus - Stern, Frank (2009)
The growing integration and participation of the Jewish population in politics, society, culture arts and religion shaped these spheres in Vienna during the time of the First Republic. Social dynamics of the young democracy, interplay of the different Jewish milieus, immigration from Eastern and Southeastern Europe as well as the growing cultural links with Berlin, Budapest, Paris and Prague made Austrian-Jewish culture in all areas of the development of the city of Vienna highly influential. Antidemocratic tendencies, especially antisemitism, influenced both the discourses on current events and inner-Jewish debates such as the role of Jewish religion, acculturation and Zionism. The publication "Wien und die jüdische Erfahrung 1900 - 1938. Akkulturation - Antisemitismus, Zionismus" initiated by Univ.-Prof. Frank Stern and Mag. Barbara Eichinger from the Institute for Contemporary History, University of Vienna, shows the state of the art of research on this subject. The publications focus placed on the current interdisciplinary inclusion of Austrian-Jewish cultural history. The volume of approx. 400 pages presents up-to-date research papers by the contributors as well as an academic discourse among the authors. In order to make this discourse possible, the editors organised a four day international conference in March 2007, where academics presented their research in themed panels and discussed them in an interdisciplinary framework with other experts. The contributions to this volume present this research takting into consideration the discussions among the colleagues at the conference. Those authors who did not participate in the conference and are partly working at American universities (a.o. Harriet Pass Freidenreich, Sander Gilman) provide an insight into current US American research on the subject. The contributions in German and English by 29 authors are organized into the following subject areas: "Society and politics between acculturation and tradition" (Steven Beller, Eleonore Lappin, Klaus Hödl, Albert Lichtblau), "Music between concert hall and film: Viennese composers of Jewish descent" (Peter Dusek, Karin Wagner), "Zionism in Vienna: between coffee house, cultural and political movement" (Dieter Hecht, Armin Eidherr, Hanno Loewy), "Cultural transfer between Vienna and Palestine/Israel" (Klaus Davidowicz, Sandra Goldstein), "Viennese Jewish milieus 1900 - 1938" (Evelyn Adunka, Peter Landesmann, Marcus G. Patka, Karin Stögner), "Women´s movements in Vienna"(Harriet Pass Freidenreich, Elisabeth Malleier, Michaela Raggam-Blesch), "Identity crises and antisemitism" (Gabriele Anderl, Elisabeth Brainin and Samy Teicher, Sander Gilman, Siegfried Mattl, Michael Laurence Miller), "Literature and theater in interwar Vienna" (Brigitte Dallinger, Werner Hanak, Birgit Peter), "The Road into the open on stage and screen (Wolfgang Müller-Funk, Murray G. Hall, Bettina Riedmann). The authors come from research centres in Belgium, Germany, Israel, the USA and Hungary as well as all current research centres on Jewish history in Austria (a.o. Institute for Jewish Studies, Vienna; Institute for History, Salzburg; Center for Jewish Cultural History, Salzburg; Institutte for the History of the Jews in Austria, St. Pölten; Center for Jewish Studies, Graz; Institute of Contemporary History, Vienna; University of Performing Arts, Vienna; Institut for German Studies, Vienna; Institut for Theater, Film and Media Studies, Vienna; Jewish Museum of the City of Vienna). The volume will be published in the anniversary year 2008 with a preface by the rector of the University of Vienna, Univ.-Prof. Dr. Georg Winckler.